Different Patterns of Neurodegeneration and Glia Activation in CA1 and CA3 Hippocampal Regions of TgCRND8 Mice - Ugolini, Filippo; Lana, Daniele; Nardiello, Pamela; Nosi, Daniele; Pantano, Daniela; Casamenti, Fiorella; Giovannini, Maria Grazia (Frontiers in Aging Neuroscience, 2018)
We investigated the different patterns of neurodegeneration and glia activation in CA1 and CA3 hippocampal areas of TgCRND8 mice. The main feature of this transgenic model is the rapid development of the amyloid pathology, which starts already at 3 months of age. We performed immunohistochemical analyses to compare the different sensibility of the two hippocampal regions to neurodegeneration. We performed qualitative and quantitative evaluations by fluorescence immunohistochemistry with double or triple staining, followed by confocal microscopy and digital image analysis in stratum pyramidale (SP) and stratum radiatum (SR) of CA1 and CA3, separately. We evaluated time-dependent Aβ plaques deposition, expression of inflammatory markers, as well as quantitative and morphological alterations of neurons and glia in transgenic mice at 3 (Tg 3M) and 6 (Tg 6M) months of age, compared to WT mice. In CA1 SR of Tg 6M mice, we found significantly more Medium and Large plaques than in CA3. The pattern of neurodegeneration and astrocytes activation was different in the two areas, indicating higher sensitivity of CA1. In the CA1 SP of Tg 6M mice, we found signs of reactive astrogliosis, such as increase of astrocytes density in SP, increase of GFAP expression in SR, and elongation of astrocytes branches. We found also common patterns of glia activation and neurodegenerative processes in CA1 and CA3 of Tg 6M mice: significant increase of total and reactive microglia density in SP and SR, increased expression of TNFα, of iNOS, and IL1β in astrocytes and increased density of neurons–astrocytes–microglia triads. In CA1 SP, we found decrease of volume and number of pyramidal neurons, paralleled by increase of apoptosis, and, consequently, shrinkage of CA1 SP. These data demonstrate that in TgCRND8 mice, the responses of neurons and glia to neurodegenerative patterns induced by Aβ plaques deposition is not uniform in the two hippocampal areas, and in CA1 pyramidal neurons, the higher sensitivity may be related to the different plaque distribution in this area. All these modifications may be at the basis of memory loss, the peculiar symptom of AD, which was demonstrated in this transgenic mouse model of Aβ deposition, even at early stages.